Pengaruh Loyalitas dan Prestasi Kerja Terhadap Promosi Jabatan pada Koperasi Peternak Garut Selatan - Paroli (Jurnal Informatika Ekonomi Bisnis, 2024)
This research departs from a phenomenon regarding employee promotions at the South Garut Breeders Cooperative (KPGS) which tend to be less than optimal. The phenomenon that occurs certainly has a cause, including loyalty and work performance. The purpose of this research is to determine the influence of Loyalty and Work Performance on Position Promotion at KPGS. The population and sample in this research were employees, totaling 39 respondents. The method used in research is descriptive and associative. Based on data analysis, information was obtained that this research instrument was declared valid because it had a value greater than the r table of 0.300 and was declared reliable because it had a Cronbach's alpha value greater than 0.600. From the results of the correlation test, it is clear that Loyalty and Work Performance have a positive influence on Position Promotion with an r value of 0.767 for loyalty and 0.783 for work performance, while the coefficient of determination is 30.2% while the remaining 69.8% is influenced by other factors. which was not examined in this study. Based on hypothesis testing using both the t test and f test, there is a positive and significant influence between loyalty and work performance on job promotion, both partially and simultaneously.